BERORIENTASI CHEMOENTREPRENEURSHIP TERHADAP PENINGKATAN HASIL BELAJAR KIMIA (Jurnal Inovasi Pendidikan Kimia, 2014)
This study aims to investigate the influence of applied practical implementation of Chemoentrepreneurship (CEP) oriented towards improvement learning outcomes on colloid chemistry subject of class XI high school students. The population of this study were all Science students of class XI of the high schools in Magelang, 2012-2013 school year. The design used in this study was pretest-posttest control group design. The sampling technique used was purposive sampling, obtained Science XI-3 as experimental class used practical methods applicable CEP oriented and Science class XI-2 as the control class. The results showed that there was an influence of applied practical implementation of CEP oriented towards thew improvement of student learning outcomes chemistry. The magnitude of the effect of applied practical implementation of CEP oriented towards improvement of student learning outcomes chemistry was 63.64%. The improvement of student learning outcomes in the experimental class in the high category with N-Gain value of 0.84 was greater than the control class with Ngain value of 0.51 was included in the medium category. Based on the results, it can be concluded that there are significant influence of practical implementation of CEP applicative oriented toward chemistry learning outcome of students in one high school in Magelang.Keywords: Applicative Experiment Method, Chemoentrepreneurship, Learning Outcomes